Hexactinellida of the genus Rossella, of ANT XXIV/2 (SYSTCO I) Expedition—Antarctic Eastern Weddell Sea - Göcke, Christian; Janussen, Dorte (Zootaxa, 2013)
The genus Rossella Carter, 1872 comprises a group of very abundant and large sponges, which often dominate and even define the benthic habitats of the Antarctic shelf. While the ecological role and importance of the genus is unquestionable, the taxonomy of Rossella has been in a state of flux since its erection in 1872. Several species have been described, many of which have proven to be individual representatives of species with high variation in diagnostic characters, thus many published species are actually synonyms and a valid concept is still lacking. Here, we present the Rossella-fauna of one station sampled during the SYSTCO-I expedition in winter 2007/08 at 600 m depth on the lower Ekström-shelf near Kapp Norvegia, Eastern Weddell Sea, Antarctica. This sponge fauna showed some remarkable peculiarities in its characters, especially an unusually large growth of many microscleres, which will broaden the diagnoses of many Rossella spp. significantly. Implications for the definitions of these species are discussed.